DELIGNIFICATION OF PAPER PULP BY PURIFIED LACCASE FROM ASPERGILLUS FLAVUS - M. S. Aslam; K. Hanif; S. U. Rehman; I. Gull; M. A. Athar; Z. Abbas (Journal of Animal and Plant Sciences, 2016)
The laccase enzyme was purified and characterized from the supernatant of the Aspergillus flavus (A. flavus) sprouting culture and its paper pulp delignification capacity was determined. The laccase production reached maximum level on 14th day of incubation in malt extract media at 40 oC. Specific activity and molecular mass of purified monomeric enzyme was found to be 780 U/mg and 40 kDa respectively. Km and Vmax values of the purified laccase were determined to be 12 µM and 3804 µM/min respectively. A. flavus laccase was strongly impeded by 5 mM L-cysteine, di-thiothreitol, Na-azide and moderately impeded by SDS and EDTA at concentration of 5 mM. Laccase activity was improved by Cu2+, Ca+2 and Mg2+ ions while impeded by K+1, Ni+2, ,NH4+1, Ba+2 and Ag+2 at 1.0 mM concentration. The delignification capacity of extracellular laccase enzyme was examined by using 2, 2-azinobis-3-ethylbenzthiazoline-6-sulfonate as a mediator.The optimum pH and temperature for paper pulp delignification were established to be 4.5 and 40°C respectively while the optimum time was found to be 2 hours.
Keywords: Laccase; Industrial Enzyme; Delignification; Paper Pulp